3′UTR polymorphisms of carbonic anhydrase IX determine the miR-34a targeting efficiency and prognosis of hepatocellular carcinoma - Kuo-Tai Hua (Nature Portfolio, 2017)
Abstract Carbonic anhydrase IX (CA9) expression level has been considered as a poor prognostic factor in hepatocellular carcinoma (HCC) patients. However, the judging criteria of CA9 level is hard to define for potential clinical applications. Unlike CA9 expression level, CA9 polymorphism is poorly documented in HCC. Here, we found that people carry A allele at CA9 rs1048638, a 3′UTR SNP, has higher risk of HCC. rs1048638-CA correlates with advanced stages, larger tumor sizes, more vascular invasion, and shorter survival of HCC patients. A allele at CA9 rs1048638 impairs miR-34a, a tumor suppressor miRNA in HCC, binding to CA9 3′UTR and desensitizes CA9 mRNA to miR-34a-dependent RNA degradation. CA9 expression levels were also correlated with miR-34a levels and rs1048638 genotypes in HCC patients. rs1048638 influences HCC risk and progression through effects on miR-34a-targeted CA9 expression in HCC. In conclusion, genetic variations of the CA9 3′UTR play important roles in regulating CA9 expression and cancer progression, which is a novel determinant and target for HCC metastasis and prognosis.